Synergistic inhibition of human glioma cell line by temozolomide and PAMAM‐mediated miR‐21i. Issue 1 (27th April 2012) - Qian, Xiao‐Min; Shi, Zhen‐Dong; Ren, Yu; Liu, Chao‐Yong; Ji, Ya‐Ru; Long, Li‐Xia; Pu, Peiyu; Sheng, Jing; Yuan, Xu‐Bo; Kang, Chun‐Sheng
Abstract Temozolomide (TMZ) is a promising chemotherapeutic agent for treating glioblastomas. However, resistance develops quickly and with a high frequency. Efforts to overcome chemoresistance are, therefore, critically needed. In present study, a poly(amidoamine; PAMAM) dendrimer was used as a vector to deliver microRNA‐21 inhibitor (miR‐21i) into U87 cells and the chemosensitivity of the combination effect of miR‐21i and TMZ for glioma therapy was investigated. Flow cytometry analysis showed the uptake efficiency of microRNA‐21 inhibitor after complexation with PAMAM. Real‐time PCR and in situ hybridization indicated that, compared with TMZ or miR‐21i treated cells, cells simultaneously treated with miR‐21i and TMZ showed a remarkable decrease in the microRNA‐21 (miR‐21) level. The transfection of miR‐21i enhanced the chemosensitivity by significantly decreasing the IC50 value of TMZ to glioma cells. Knockdown of miR‐21 promoted the cells' apoptosis, and at the same time, inhibited cell invasion. In conclusion, the combination treatment of glioma cells with TMZ and miR‐21i could yield a synergistic effect in inhibition of human glioma cell line. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2012